PENGARUH PEMBERIAN SUSPENSI MENIRAN (Phyllanthus niruri L.) TERHADAP KERUSAKAN HEPAR TIKUS PUTIH YANG DIINDUKSI ANTITUBERKULOSIS RIFAMPISIN DAN ISONIAZID - Sulistyoningrum, Evy; Pribadi, Fajar Wahyu (MANDALA of Health, 2010)
Tuberculosis treatment required at least two antituberculosis drugs (ATDs) and long term course.Isoniazid (INH) and Rifampicin are the two most active ATDs and were used in whole course of treatment.INH and Rifampicin combination increased risk of hepatotoxixity. Meniran (Phyllanthus niruri L.) containsphyllanthin, active subtance that is believed to have hepatoprotective activity. The aim of this study was toknow the effect of meniran suspension on AST/ALT blood levels and histopathological findings afterinduction of Rifampicin and INH. Twenty five male albino rats (Rattus norvegicus) wistar strain aged twomonths and weighed 150-200 grams were divided into five groups of five each. Positive control (A) wastreated with aquadest, negative control (B) was treated with Rifampicin and INH; one dose meniran (I) waspre-treated with 16,2 mg meniran before ATDs; two dose meniran (II) was pre-treated with 32,4 mg meniranbefore ATDs, three dose meniran (III) was pre-treated with 48,6 mg meniran before ATDs. The drugs wereadministered orally for 28 days. Blood samples for ALT/AST levels and histopathology sample were taken atthe end of study. One way ANOVA, post hoc and linear regression were used for data analysis. There wassignificant mean difference for ALT levels (p=0,000) but not for AST level (p> 0,05). Increasing dose ofmeniran decreased serum level of ALT (r=-0,539). Vacuolar degeneration, necrosis and portal triadleucocytes infiltration were most common in negative control groups, while these changes were reduced inmeniran-treated groups. We can conclude that meniran pretreatment reduces INH-rifampicin-inducedhepatotoxicity.